Calophyllum inophyllum: A Comprehensive Analysis of its Ethnobotanical, Phytochemical, and Pharmacological Properties - Farida, Sofa; Jenie, Riris Istighfari; Fakhrudin, Nanang (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Nyamplung (Calophyllum inophyllum L.) is reported to have ethnomedicinal benefits in traditional medicine systems. Leaves, fruit, seeds, flowers, stems, roots and essential oils are the parts that are often used. Previous scientific studies revealed that this plant part is a valuable resource of secondary metabolites and exhibits a wide range of biological activities. The purpose of this review is to deliver thorough and detailed insights into the traditional uses, chemical ingredients, biology, and pharmacological studies as scientific evidence about the useful efficacy of C. inophyllum in the development of modern medicine. Traditional use shows C. inophyllum is widely used to treat skin diseases, wounds, boils, vaginal discharge, bleeding, gonorrhea, chronic bronchitis, sore eyes, heatstroke, and headaches. C. inophyllum is rich in phenols, polyphenols, flavonoids, xanthones, coumarins, and terpenoids. Several research results show that C. inophyllum possesses a multitude of pharmacological properties including anti-cancer, anti-inflammatory, antimicrobial, antioxidant, antiplatelet, antiviral, and antidiabetic activities.